Investigation and optimization of PET-guided SPECT reconstructions for improved radionuclide therapy dosimetry estimates - Marquis, Harry; Willowson, Kathy P.; Schmidtlein, C. Ross; Bailey, Dale L. (Frontiers in Nuclear Medicine, 2023)
Aims: To investigate and optimize the SPECTRE (Single Photon Emission Computed Theranostic REconstruction) reconstruction approach, using the hybrid kernelized expectation maximization (HKEM) algorithm implemented in the software for tomographic image reconstruction (STIR) software library, and to demonstrate the feasibility of performing algorithm exploration and optimization in 2D. Optimal SPECTRE parameters were investigated for the purpose improving SPECT-based radionuclide therapy (RNT) dosimetry estimates. Methods: Using the NEMA IEC body phantom as the test object, SPECT data was simulated to model an early and late imaging time point following a typical therapeutic dose of 8 GBq of 177Lu. A theranostic 68Ga PET-prior was simulated for the SPECTRE reconstructions. The HKEM algorithm parameter space was investigated for SPECT-unique and PET-SPECT mutual features to characterize optimal SPECTRE parameters for the simulated data. Mean and maximum bias, coefficient of variation (COV %), recovery, SNR and root-mean-square error (RMSE) were used to facilitate comparisons between SPECTRE reconstructions and OSEM reconstructions with resolution modelling (OSEM_RM). 2D reconstructions were compared to those performed in 3D in order to evaluate the utility of accelerated algorithm optimization in 2D. Segmentation accuracy was evaluated using a 42% fixed threshold (FT) on the 3D reconstructed data. Results: SPECTRE parameters that demonstrated improved image quality and quantitative accuracy were determined through investigation of the HKEM algorithm parameter space. OSEM_RM and SPECTRE reconstructions performed in 2D & 3D were qualitatively and quantitatively similar, with SPECTRE showing an average reduction background COV % by a factor of 2.7 and 3.3 for the 2D case and 3D case respectively. The 42 % FT analysis produced an average % volume difference from ground truth of 158 % and 26 %, for the OSEM_RM and SPECTRE reconstructions, respectively. Conclusions: The SPECTRE reconstruction approach demonstrates significant potential for improved SPECT image quality, leading to more accurate RNT dosimetry estimates when conventional segmentation methods are used. Exploration and optimization of SPECTRE benefited from both fast reconstruction times afforded by first considering the 2D case. This is the first in-depth exploration of the SPECTRE reconstruction approach, and as such, it reveals several insights for reconstructing SPECT data using PET side-information.